Protein-induced fluorescence enhancement of two-photon excitable water-soluble diketopyrrolopyrroles. Issue 31 (26th July 2017) - Tang, Simon; Ghazvini Zadeh, Ebrahim H.; Kim, Bosung; Toomey, Nikia T.; Bondar, Mykhailo V.; Belfield, Kevin D.
Abstract : Water soluble diketopyrrolopyrrole one- and two-photon fluorescent probes were prepared in high yield exhibiting fluorescence switch-on upon protein binding. Abstract : Fluorescent contrast agents are important tools in cell biology and medical imaging due to their high sensitivity and relative availability. Diketopyrrolopyrrole (DPP) derivatives have been recently studied for applications in bioimaging, but certain drawbacks due to their inherent structure have stifled progress towards their widespread implementation. Aggregation caused quenching (ACQ) associated with π–π stacking in relatively rigid extended conjugation systems as well as hydrophobicity of previously reported DPPs make most unsuitable for biological imaging applications. Addressing these deficiencies, we report the synthesis and photophysical characterization of two new water-soluble diketopyrrolopyrole (DPP) probes that exhibit pronounced protein-induced fluorescence enhancement (PIFE) upon binding serum albumin protein. In vitro studies were also performed showing low cytotoxicity for the new DPP probes. Two-photon fluorescence microscopy (2PFM) images were obtained via excitation at 810 nm and emission in the NIR window of biological transparency, illustrating the potential of these compounds as nonlinear optical bioimaging probes.